A Cross-Sectional Study of Hypertension and Associated Factors in Young MBBS Students at a Tertiary Care Institute - Saran, Aditya; Puri, Sarika (International Journal of Medical Students, 2025)
BACKGROUND: Hypertension is increasingly prevalent among young adults, including MBBS students, who are often unaware of their condition. The silent progression of hypertension is a critical issue due to its association with cardiovascular diseases. There is a scarcity of research focusing on the prevalence and risk factors of hypertension among young MBBS students in India. This study aims to evaluate the prevalence of hypertension and its related factors among MBBS students at a tertiary care institution in Mumbai, India. METHODS: A cross-sectional study was conducted among 250 MBBS students aged 18 to 24, selected based on predefined eligibility criteria. Blood pressure was measured using the standard auscultatory method following a 10-minute rest period. Hypertension classification was done as per JNC-VII guidelines. Various associated risk factors, including lifestyle and family history, were documented in case study forms. Statistical analysis was performed to explore correlations between these factors and hypertension. RESULTS: The study identified substantial rates of pre-hypertension (32.40%) and hypertension (25.20%) among the participants, with 22% classified as Stage I and 3.20% as Stage II hypertensive, as illustrated in the Figure. Alarmingly, 53.60% of those with hypertension were unaware of their condition. Significant risk factors included alcohol/tobacco use (34.40%), abdominal obesity (47.60%), family history (46.80%), and unhealthy lifestyle practices. Statistically significant associations were observed between pulse rate (p-value = 0.012), waist-to-hip ratio (p-value = 0.019), alcohol or tobacco consumption (p-value < 0.0001), and hypertension. CONCLUSION: The study underscore the high prevalence of pre-hypertension and hypertension among young MBBS students in Mumbai, highlighting the urgent need for early detection and preventive measures. Regular monitoring of blood pressure and increased awareness about hypertension are essential to mitigate the long-term cardiovascular risks in this population.